2017
DOI: 10.1016/j.tranon.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Stem-Like Cancer Cells in Primary Endometrial Cancer Using Cell Surface Markers CD133 and CXCR4

Abstract: Endometrial cancer (EC) is the most common familiar gynecologic malignant tumor identified in the female reproductive system and has been increasing yearly. In this study, we will identify the surface markers and stem cell markers related with cancer stem cells (CSCs) of EC. Tissue samples were obtained from endometrial cancer patients during surgical procedures. Single cells were isolated from the tissues for culturing, transfection into nude mice, and histopathology analysis. RT-PCR demonstrated that the cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 47 publications
4
26
0
1
Order By: Relevance
“…Kimura et al found CXCR4 was associated with cell proliferation and tumorigenicity, concluding that CXCR4 is the marker of synovial sarcomainitiating cells, a new biomarker for prognosis and a new potential therapeutic target (28). Sun et al demonstrated that CD133 + CXCR4 + primary endometrial cancer cells grew faster, exhibited high expression of stemness-related genes, produced more spheres, had higher clonogenic ability, and more resistant to anti-cancer drugs than other subpopulations, indicating that CD133 + CXCR4 + cells may possess some characteristics of CSCs in primary endometrial cancer (29). CXCR4 increases the growth and sphere formation efficiency of hypoxic breast cancer side population (SP) cells by c-Jun/ABCG2 pathway (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kimura et al found CXCR4 was associated with cell proliferation and tumorigenicity, concluding that CXCR4 is the marker of synovial sarcomainitiating cells, a new biomarker for prognosis and a new potential therapeutic target (28). Sun et al demonstrated that CD133 + CXCR4 + primary endometrial cancer cells grew faster, exhibited high expression of stemness-related genes, produced more spheres, had higher clonogenic ability, and more resistant to anti-cancer drugs than other subpopulations, indicating that CD133 + CXCR4 + cells may possess some characteristics of CSCs in primary endometrial cancer (29). CXCR4 increases the growth and sphere formation efficiency of hypoxic breast cancer side population (SP) cells by c-Jun/ABCG2 pathway (30).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies, we found that CXCR4 was significantly up-regulated in ESCC tissues, and correlated with tumor invasion and survival. Increasing evidence suggests that CXCR4 is potentially the CSCs marker of malignant tumors including synovial sarcoma (28), endometrial cancer (29), lung cancer (34), and so on. To investigate the role of CXCR4 in ESCC, we isolated CXCR4 positive and negative cells by MACS.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that the aberrant expression of ALDH1 contributes to cancer stem cell transformation from less aggressive cancer with the association of CD133 [ 61 , 62 ]. Moreover, CD133 + and CXCR4 + are reported to involve in cancer stem cell phenotype in various cancer types [ 63 , 64 , 65 ]. Thus, targeting ALDH1 , CRCR4, and CD133 could provide us a possibility to target cancer stem cell population.…”
Section: Discussionmentioning
confidence: 99%
“…The intrinsic characteristics of cells to generate clones in two-dimensional systems most likely also allows these cells to form spheres in a three-dimensional setting. Sun and coworkers have shown that the same specific subset of endometrial cancer cells displaying CSC surface markers were able to form both, numerous spheres and numerous colonies compared to the other cellular populations investigated [ 9 ]. Moreover, we were recently able to demonstrate that PTC-209 not only abolished clonogenic growth in BTC cells but also reduced sphere formation potential [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The assay was originally used to study the effects of radiation on cellular survival and growth [ 4 , 5 ]. Today, clonogenic assays are used for a variety of experimental questions, especially in tumor biology [ 6 , 7 , 8 , 9 , 10 ]. Albeit, two-dimensional cell culture assays do not fully recapitulate the physiologic three-dimensional growth of tumor cells, the ability to generate clones is interpreted as a trait of aggressive tumor cells that harbor tumor-initiating capabilities [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%